Pediatric CIDP: Diagnosis and Management. A Single-Center Experience - Łukawska, Małgorzata; Potulska-Chromik, Anna; Lipowska, Marta; Hoffman-Zacharska, Dorota; Olchowik, Beata; Figlerowicz, Magdalena; Kanabus, Karolina; Rosiak, Edyta; Kostera-Pruszczyk, Anna (Frontiers in Neurology, 2021)
Background: Chronic inflammatory demyelinating polyneuropathy (CIDP) is a rare acquired polyneuropathy that especially among youngest children should be differentiated with hereditary neuropathies. Even though upon diagnosis treatment options are similar in children and adults, diagnostic challenges are faced in the pediatric population. Methods: We conducted a retrospective analysis of clinical symptoms, nerve conduction study results, modes of treatment, and final outcome in 37 children aged 3.5–17 years with a final diagnosis of CIDP (18 girls, 19 boys). We established three groups of patients based on age at onset of CIDP: 0–4, 4–13, and 13–18 years. Follow-up ranged from 10 to 222 months. Results: In our analysis, 19/37 patients (51.4%) had an atypical presentation: distal variant of CIDP in 12/37 patients (32.4%) and pure motor variant of CIDP in 5/37 patients (13.5%), and one patient had a pure sensory variant (1/37, 2.7%). Furthermore, 3/37 patients (8.1%) had additional concurring symptoms, including involuntary movements of face muscles (1/37, 2.7%) or hand tremor (2/37, 5.4%). During the follow-up, 23/37 patients (62.2%) received intravenous immunoglobulin (IVIg); 22/37 patients (59.5%) received steroids, 6/37 patients (16.2%) received IVIg and steroids, and 12/37 patients (32.4%) received immunosuppressive drugs, mostly azathioprine, but also methotrexate and rituximab. One patient was treated with plasmapheresis. Complete remission was achieved in 19/37 patients (51.4%) with CIDP in its typical form. Remission with residual symptoms or minimal deficit was observed in 4/37 patients (10.8%), whereas 14/37 patients (37.8%) remain on treatment with gradual improvement. Conclusion: Childhood CIDP may occur in its typical form, but even ~50% of children can present as an atypical variant including distal, pure motor, or pure sensory. Most children have a good prognosis; however, many of them may require long-term treatment. This highlights the importance of an early diagnosis and treatment for childhood CIDP.